2011
DOI: 10.1111/j.1740-0929.2011.00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin‐10 stimulates the release of luteinizing hormone and testosterone in pre‐ and post‐pubertal male goats

Abstract: The aims of the present study were to clarify the effect of kisspeptin-10 (Kp10) on the secretion of luteinizing hormone (LH) and testosterone (T) in pre-pubertal and post-pubertal male ruminants. Four male goats (Shiba goats) were given an intravenous (i.v.) injection of Kp10 (5 µg/kg body weight (b.w.)), gonadotoropin-releasing hormone (GnRH, 1 µg/kg b.w.), or 2 mL of saline as a control at the ages of 3 (pre-pubertal) and 6 (post-pubertal) months. A single i.v. injection of Kp10 significantly stimulated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 24 publications
3
16
1
2
Order By: Relevance
“…A single dose of Kiss-54 was reported to cause ovulation in rats (30) and to significantly increase sex steroid levels in prepubertal fish (31). Gonadotropin increases were registered following a single IV or IM dose of Kiss-10 in prepubertal cats (32), sheep (33), and goats (34). It was reported that Kiss-10 given at varying doses reduces testosterone levels, a reduction that was attributed to testicular degeneration rather than a fall in LH secretion (25).…”
Section: Discussionmentioning
confidence: 99%
“…A single dose of Kiss-54 was reported to cause ovulation in rats (30) and to significantly increase sex steroid levels in prepubertal fish (31). Gonadotropin increases were registered following a single IV or IM dose of Kiss-10 in prepubertal cats (32), sheep (33), and goats (34). It was reported that Kiss-10 given at varying doses reduces testosterone levels, a reduction that was attributed to testicular degeneration rather than a fall in LH secretion (25).…”
Section: Discussionmentioning
confidence: 99%
“…The plasma LH response to GnRH was about 3 times higher and the FSH response 1.5 times higher than the response to the same dose of KP-10. In contrast, in pre-and post-pubertal male goats there was no difference in the plasma profiles of LH and testosterone after the administration of GnRH or KP-10 [46] . FSH concentration also rose rapidly after canine KP-10 administration.…”
Section: Canine Kp-10 Stimulation Of Lh Fsh and Oestradiolmentioning
confidence: 62%
“…The response to exogenous KP-10 may be influenced by the phase of the oestrous cycle, the pubertal stage and the sex steroid environment [14,39,42,46] . The sensitivity of the canine pituitary to GnRH increases during the progression of anoestrus [35] and it is probable that the response to KP-10 may differ during the different phases of the cycle, since gonadal hormones exert positive or negative feedback on GnRH production and secretion.…”
Section: Canine Kp-10 Stimulation Of Lh Fsh and Oestradiolmentioning
confidence: 99%
“…Nos sistemas de criação de suínos brasileiros, as fêmeas destinadas à reprodução que não conseguem expressar o estro até os 8 meses de idade são frequentemente descartadas do plantel (eNgbLoM et al, 2007;staNcic et al, 2011). Consequentemente, a administração de kisspeptina poderia acelerar a manifestação do estro e a ovulação nesses animais.…”
Section: Resultsunclassified
“…Em ovelhas pré-puberes, a administração intermitente de kisspeptina aumenta a secreção de LH para níveis comparáveis aos de fêmeas cíclicas adultas (redMoNd et al, 2011). Da mesma forma, a injeção única de kisspeptina induz uma descarga de LH em porcas e cabras pré-púberes (LeNts et al, 2008;saito et al, 2012), sendo que nas cabras essa resposta foi de maior intensidade em comparação aos animais púberes. Em função desses resultados, nossa hipótese é que a injeção de kisspeptina pode ser utilizada para induzir a ovulação de fêmeas suínas pré-púberes previamente estimuladas com eCG.…”
Section: Introductionunclassified